Enhancing protective immunity to malaria with a highly immunogenic virus-like particle vaccine - Gilbert, S; Collins, K; Snaith, R; Cottingham, M; Hill, A (Nature Publishing Group, 2017)
The leading malaria vaccine in development is the circumsporozoite (CS) protein-based vaccine, RTS,S, which targets the pre-erythrocytic stage of Plasmodium falciparum infection. It induces modest levels of protective efficacy largely mediated by CS specific antibodies. We aimed to enhance vaccine efficacy by generating a potentially more immunogenic CS-based particle vaccine and developed a next-generation RTS,S-like vaccine, called R21. The major improvement is that in contrast to RTS,S, R21 particles are formed from a single CS-HBsAg fusion protein and this leads to a vaccine composed of a much higher proportion of CS antigen than RTS,S. We demonstrate that in BALB/c mice R21 is immunogenic at very low doses and when administered with the ISCOM adjuvants Abisco-100 and Matrix-M it elicits sterile protection against transgenic sporozoite challenge. In addition, in contrast to RTS,S, only a minimal antibody response to the HBsAg carrier was induced. Concurrent induction of cellular and humoral immune responses was also achieved by combining R21 with TRAP-based viral vectors and protective efficacy was significantly enhanced. These studies identify an anti-sporozoite vaccine component that may outperform RTS,S and R21 is now under evaluation in Phase 1/2a clinical trials.